RESOLUSI KONFLIK DUNIA USAHA DENGAN MASYARAKAT Kajian Sosial Budaya Resolusi Konflik antara Perkebunan Kelapa Sawit dengan Petani Plasma dan Masyarakat Dayak di Provinsi Kalimantan Barat - Oetami Dewi (Politeknik Kesejahteraan Sosial, 2007)
Oil-palm estates are believed by the government as a business undertaking to boost thewell-being of the peasants and provide job opportunities in rural areas. Oil-palm estates are also believed to be able to boost economic growth of provinces. In establishing oil-palm estates, the government prompts cooperation pattern between the capital holders (private companies) and the local farmers in model called Peopleâ€™s Nucleus Estates (Perusahaan Inti Rakyat â€“ PIR) in which the company provides the capital, technology and the management of marketing, while the local farmers provide the lands and the labour.West Kalimantan is a region preferred to develop oil-palm estates for the vast area of â€œno manâ€™s vacant landsâ€ and the oil-palm estate companies are expected to conduct the transfer of technology to the local horticulturalists (agriculturalists with Swidden/slash burn cultivation) so that the well-being of the locals get increased. This paper describes that the plasma smallholding plantation planters need more affirmative from the state to protect not only their land but also their culture to increase economic and social development for their social welfare. The problems started when the communal lands the local communities managed as agricultural lands to sustain their life and as reserves for additional income were taken over by the company. As the population number of the plasma smallholding plantation plantersâ€™ family grew while the oil-palm at their smallholding plantation produced less and less due to the old age, the planters assumed that the company had no attention to the plantersâ€™ economic problems.Key Words : the plasma smallholding plantation, Peopleâ€™s Nucleus Estates